2010
DOI: 10.1111/j.1600-0560.2010.01517.x
|View full text |Cite
|
Sign up to set email alerts
|

Value of p63 and podoplanin (D2‐40) immunoreactivity in the distinction between primary cutaneous tumors and adenocarcinomas metastatic to the skin: a clinicopathologic and immunohistochemical study of 79 cases

Abstract: The distinction of metastatic carcinomas to the skin from poorly differentiated primary cutaneous carcinomas and sometimes primary benign adnexal tumors can pose a significant diagnostic challenge. The purpose of this study was to evaluate the role of p63 and podoplanin (D2-40) immunoreactivity for separating primary skin tumors vs. cutaneous metastases of carcinomas from internal organs. Thirty seven primary tumors and 42 cutaneous metastatic adenocarcinomas were evaluated. The 37 primary cutaneous tumors inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
54
2
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(62 citation statements)
references
References 24 publications
3
54
2
2
Order By: Relevance
“…[15][16][17][18][19][20][21] These findings suggest that podoplanin plays a role in the progression of epithelial cancer. However, the exact molecular function of cancer cell-expressed podoplanin is currently studied.…”
Section: Discussionmentioning
confidence: 89%
“…[15][16][17][18][19][20][21] These findings suggest that podoplanin plays a role in the progression of epithelial cancer. However, the exact molecular function of cancer cell-expressed podoplanin is currently studied.…”
Section: Discussionmentioning
confidence: 89%
“…Se utiliza también para demostrar la naturaleza linfática de los vasos conteniendo células neoplásicas en su luz en émbolos tumorales, tanto de tumores cutáneos primarios como de metástasis cutáneas. También es útil para diferenciar histopatológicamente neoplasias cutáneas primarias, especialmente adenocarcinomas anexiales, de metástasis cutáneas de adenocarcinomas de vísceras internas, ya que la podoplanina se expresa en las células neoplásicas de los primeros, pero no de los segundos 47,48 . Por último, estudios recientes han propuesto utilizar este marcador junto con otros marcadores endoteliales, como Lyve-1 y CD31 en la predicción de metástasis en el ganglio centinela de melanomas, valorando la invasión intralinfática del tumor primario 49 .…”
Section: Figura 25unclassified
“…In a recent paper, p63 stained all sebaceous and NSLs, 11 and 7, respectfully [21], while a separate study found that all 16 metastatic renal cell carcinomas were negative for this antibody [55]. In addition, three primary sebaceous carcinomas of the skin in several recent studies also stained with p63 [54,56,57]. Therefore, it appears that a positive p63 stain likely eliminates the possibility of a metastasis from a renal primary.…”
Section: Differential Diagnosismentioning
confidence: 97%